Rekontekstualisasi Ide Pendidikan Perempuan Buya Hamka: Studi Analisis Hermeneutika Gracia - Abby Janu Ramadhan Abby; Alifatul Lusiana Uswatun Chasanah (IAIN PAREPARE, 2021)
Various issues regarding gender inequality against women have become issues that have not been discussed. The background for writing the article is the awareness that education is an alternative in addressing the problem of gender inequality. However, the gender-imbalanced education system is another problem. This article aims to recontextualize Buya Hamka's ideas and thoughts on women's education to be associated with the current phenomenon of women's education. Using a literature review research method, this article describes the phenomenon of gender inequality in today's education along with the idea of ​​Buya Hamka's women's education as an analysis to find good Islamic education for women to realize gender equality.